Identification of active [overlineURC] sinusoidal oscillator circuit - Pirajananchai, Virote (Frontiers in Engineering Innovation Research, 2003)
Many sinusoidal oscillators can be represented by the structure RC-CR-Active Circuits (Wien-Bridge, Twin-T). In this paper discusses a different approach is presented new structure Uniformly Distributed RC line [overlineURC] Active circuit in used oscillators may be also improved, extending their range of operation oscillator and reducing the harmonic distorton. The theory of operation of the device circuit, experimental verification of theory. This structure [overlineURC] Active oscillator has the advantage of being very small, simple to fabricate and easy to use in conjunction with microelectronic integrated circuit or Thin-Film LSI Technology.